The effect of synthetic fungicide on disease severity and plant growth of chili pepper (Capsicum annuum L.) infected with Phytophthora capsici - Rizkita Rachmi Esyanti; Nadya Farah; Faiz, Muhammad Fakhri; Muthia Gassani Verdianti; Sunardi; Safitri, Ramadhani (Penerbit Universiti Kebangsaan Malaysia, 2020)
Phytophthora blight caused by Phytophthora capsici is one of the damaging diseases that cause major loss in chili pepper (Capsicum annuum L.) production worldwide. Some synthetic fungicides containing Metalaxyl-M were reported to be able to control the pathogen’s growth. In order to evaluate the effect of synthetic fungicide on disease severity index (DSI) and plant growth of chili pepper plants after inoculation with P. capsici (104 zoospores/ml), four cultivars were used namely Laba, Pilar, Arimbi and Imola. Each cultivar was treated with a synthetic fungicide and P. capsici (FP), with P. capsici-only (P) and uninoculated plants (C) were used as controls. The result showed that the application of synthetic fungicide was able to control the pathogen’s growth, indicated by the decreased DSI. The application of synthetic fungicide was also able to preserve the growth of chili pepper plants, indicated by the plant height and number of leaves, even after the infection with P. capsici. In conclusion, the application of synthetic fungicide was effective in controlling the growth of P. capsici while preserving the growth of chili pepper plants in cultivar Pilar, Imola, Laba, and Arimbi.